ZmnMAT1, a nuclear-encoded type I maturase, is required for the splicing of mitochondrial Nad1 intron 1 and Nad4 intron 2 - Fan, Kaijian; Fu, Qinghui; Wei, Qianhan; Jia, Sinian; Zhao, Anqi; Wang, Tengteng; Cao, Jie; Liu, Yan; Ren, Zhenjing; Liu, Yunjun (Frontiers in Plant Science, 2022)
Maturases can specifically bind to intron-containing pre-RNAs, folding them into catalytic structures that facilitate intron splicing in vivo. Plants possess four nuclear-encoded maturase-related factors (nMAT1-nMAT4) and some maturases have been shown to involve in the splicing of different mitochondrial group II introns; however, the specific biological functions of maturases in maize are largely uncharacterized. In this study, we identified a maize ZmnMAT1 gene, which encodes a mitochondrion-localized type I maturase with an RT domain at N-terminus and an X domain at C-terminus. Loss-of-function mutation in ZmnMAT1 significantly reduced the splicing efficiencies of Nad1 intron 1 and Nad4 intron 2, and showed arrested embryogenesis and endosperm development, which may be related to impaired mitochondrial ultrastructure and function due to the destruction of the assembly and activity of complex I. Direct physical interaction was undetectable between ZmnMAT1 and the proteins associated with the splicing of Nad1 intron 1 and/or Nad4 intron 2 by yeast two-hybrid assays, suggesting the complexity of group II intron splicing in plants.